Risk prediction and assessment: Duration, infections, and death toll of the COVID-19 and its impact on China's economy - Xiao-Guang Yue; Xue-Feng Shao; Rita Yi Man Li; M. James C. Crabbe; Lili Mi; Siyan Hu; Julien S. Baker; Liting Liu; Kechen Dong (Journal of Risk and Financial Management, 2020)
This study first analyzes the national and global infection status of the Coronavirus Disease that emerged in 2019 (COVID-19). It then uses the trend comparison method to predict the inflection point and Key Point of the COVID-19 virus by comparison with the severe acute respiratory syndrome (SARS) graphs, followed by using the Autoregressive Integrated Moving Average model, Autoregressive Moving Average model, Seasonal Autoregressive Integrated Moving-Average with Exogenous Regressors, and Holt Winter's Exponential Smoothing to predict infections, deaths, and GDP in China. Finally, it discusses and assesses the impact of these results. This study argues that even if the risks and impacts of the epidemic are significant, China's economy will continue to maintain steady development.
Keywords: 330; autoregressive integrated moving average model; autoregressive moving average model; China's economy; COVID-19; GDP; Holt Winter's exponential smoothing; seasonal autoregressive integrated moving-average with exogenous regressors; severe acute respiratory syndrome